GENETIC PERFORMANCE OF THE STRIPED CATFISH (Pangasianodon hypophthalmus Sauvage, 1878) POPULATION DERIVED FROM SELECTIVE BREEDING - Huria Marnis; Evi Tahapari; Jadmiko Darmawan (Indonesian Aquaculture Journal, 2019)
Selective breeding to improve growth trait in striped catfish (Pangasianodon hypophthalmus) need genetic performance data. This study was carried out to evaluate genetic performance of different generations of the striped catfish population derived from selective breeding. Fifty fish of each population from four generations selected striped catfish was analyzed using five microsatellite loci (Pg-1, Pg-2, Pg-3, Pg-13, and Pg-14). Microsatellite allele data were analyzed using Microsoft Excel, Arlequin, and Fstat software. A neighborhood joining dendrogram was constructed based on Nei’s distance (Da) matrix with 1,000 bootstrap replications using MEGA7 software. The result showed that totally 31.5 exist, ranged from 4-7. Number of allele was ranged from 5.0 to 5.2, and polymorphic data was from 0.45-0.60. There were some exception, such as the allele of the loci Pg-2—194 bp, Pg-13—227 bp, Pg-13—229 bp, and Pg-14—279 bp; their gene frequencies were increased by generation. Further analyses indicated that most genetic variations arise from individuals within populations (approximately 57.10%). The founder generation closely related to G-0 generation. Likewise, G-1 generation closely related to G-2 generation. This result indicated that selection activity had a very significant impact on the genetic improvement of the selected population.